Determining the Factors Affecting Farmers’ Decision on Organic Livestock - Nuray Demir; Canan Sancar; Okan Demir; Vecihi Aksakal; Adem Aksoy (Turkish Journal of Agriculture: Food Science and Technology, 2016)
In this study, the objective was to determine the factors affecting farmers’ decisions on organic livestock. Within this scope, the Gümüşhane province, in which one of the major organic livestock projects has been carried out, was taken into the focus of attention for this study. The data of the study was obtained from 134 surveys based on census and focusing on farmers doing conventional animal breeding and possessing 25 or more cattle. The data obtained were used in predicting the Logit Model. In the model, it was determined that the inclination to transition to organic animal breeding in institutions where the rate of benefiting from animal breeding supports and the rate of meeting forage requirements from their own are high and besides where the rate of using industrial feed is low. As a result, it was recommended that the government support for forage crops, which are already within the current support policies, should be increased on yearly basis. This will have a positive effect on the decision of the farmers to choose organic livestock. This support is also important in terms of carrying out livestock activities in more profitable and technical way.